List upon list: The ship passenger records and immigration research. - Swierenga, Robert P. (Journal of American Ethnic History)
Assesses the collection of ship passenger records for immigration research in the United States. Historical potential of ship records; Publications of ship passenger records; Ship passenger records before 1820; Contributions of Peter Wilson Coldham in the recording of English persons who migrated to the American colonies; Problems in collecting the records.